Toxicity and anti-tumour activity of organotin (IV) compounds - Abdualbasit M. Graisa (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Organotins are widely described as anti-tumor, anti-inflammatory, anti-fungal, andantimicrobial agents. In addition to their uses in biomedical fields, organotins arealso used in agricultural and industrial applications. These materials are more toxicthan inorganic cans, which are poorly absorbed and are excreted on the surface ofthe can, and cause toxicity to a variety of organisms and damage the environment.This review focuses on organotin’s toxicity and uses in biomedical fields.